The Influence of Cultivation Techniques on Horticultural Cultivation on The Diversity, Abundance, and Composition of Spiders - Salsabila, Shevira Satria; Rahardjo, Bambang Tri (University of Brawijaya, 2026)
Organic farming is a cultivation technique that applies natural materials and does not use chemical fertilizers and pesticides in cultivation techniques. Differences in cultivation techniques can affect the diversity, abundance, as well as the composition of spiders. This study was conducted to determine the diversity, abundance, as well as composition of spiders can be influenced by different cultivation techniques. The research was conducted from September 2023 to October 2023. Observations were made on organic land and conventional land. Data collection of cultivation techniques is carried out by interviews. Population and diversity data collection is carried out every 5 days within 4 weeks. Specimen collection is carried out by passive and active methods and then identification is carried out. Tabulate data in Microsoft Excel, then analyze it using Rstudio. In the Rstudio analysis, the Shapiro-Wilk test was carried out to determine the normality of the data, further Honest Significant Difference test at the level of 5%. Data analysis carried out in the form of variety analysis or and ANOSIM using the Bray-Curtis test. The results of the study, the number of spiders on organic land was more, namely 65 individuals consisting of 5 orders and 9 morphospecies. The results showed that differences in cultivation techniques had an effect on the diversity and abundance of spiders. The composition of the land shows that there is a significant difference but there are intersecting parts that indicate a similarity in the composition of spiders. The results of data analysis show that organic land has more diversity, abundance, and spider composition than conventional land.